Hydrodynamic experiments on a small-scale circulating fluidised bed reactor at elevated operating pressure, and under An O2/Co2 environment - Sarbassov, Yerbol; Zayoud, Azd; Mahanta, Pinakeswar; Gu, Sai; Ranganathan, Panneerselvam; Saha, Ujjwal (VINČA Institute of Nuclear Sciences, 2017)
Pressurised circulating fluidised bed (CFB) technology is a potentially promising development for clean coal technologies. The current work explores the hydrodynamics of a small-scale circulating fluidised bed at elevated operating pressures ranging from 0.10 to 0.25 MPa. The initial experiments were performed at atmospheric pressure with air and O/CO environments as the fluidisation gas to simulate the hydrodynamics in a CFB. A comparison between the effects of air and O/CO mixtures on the hydrodynamics was outlined in this paper for particles of 160 μm diameter. A small but distinct effect on axial voidage was observed due to the change in gas density in the dense zone of the bed at lower gas velocity, while only minimal differences were noticed at higher gas velocities. The hydrodynamic parameters such as pressure drop and axial voidage profile along the height were reported at two different bed inventories (0.5 and 0.75 kg) for three mean particle sizes of 160, 302 and 427 μm and three superficial gas velocities. It was observed that the operating pressure had a significant effect on the hydrodynamic parameters of bed pressure drop and axial bed voidage profiles. The effect of solids loading resulted in an exponential change in pressure drop profile at atmospheric pressure as well as at elevated pressure. The experimental results on hydrodynamic parameters are in reasonable agreement with published observations in the literature.
Keywords: Circulating fluidised bed; Axial voidage profile; Pressure drop; O2/CO2 mixture; Pressurised circulating fluidised bed